2013
DOI: 10.2174/157489213805290628
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory Estrogen Level Protects Against Breast Cancer in Obese Women

Abstract: Literary data suggest apparently ambiguous interaction between menopausal status and obesity-associated breast cancer risk based on the principle of the carcinogenic capacity of estrogen. Before menopause, breast cancer incidence is relatively low and adiposity is erroneously regarded as a protective factor against this tumor conferred by the obesity associated defective estrogen-synthesis. By contrast, in postmenopausal cases, obesity presents a strong risk factor for breast cancer being mistakenly attributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 108 publications
(140 reference statements)
0
41
0
Order By: Relevance
“…This hypothesis, however, fails to fully explain the relationship between body mass and breast cancer incidence and poor clinical outcome, as the relationship is present in ER-negative breast cancers [34,36]. Also, some recent studies have indicated that circulating estrogens may protect against the development of breast cancer in obese women [40]. …”
Section: Obesity and Cancermentioning
confidence: 99%
“…This hypothesis, however, fails to fully explain the relationship between body mass and breast cancer incidence and poor clinical outcome, as the relationship is present in ER-negative breast cancers [34,36]. Also, some recent studies have indicated that circulating estrogens may protect against the development of breast cancer in obese women [40]. …”
Section: Obesity and Cancermentioning
confidence: 99%
“…It has also been reported that estrogen may have protecting effects against various cancers [9]- [10]. The research revealed that estrogen has improving effects on glioblastoma treatment [11].…”
Section: Discussionmentioning
confidence: 94%
“…Docking studies enhanced ligand precision and even though drug produces unsatisfactory desired effects by binding with another macromolecules, it is possible to dwindle affinity to the opposing site so as to achieve prolonged curative effect [25]. The computational scrutiny of the selected 11 curcuminoids and the standard drug megestrol acetate was useful to identify its likeliness to the protein selected p53.…”
Section: Resultsmentioning
confidence: 99%